The conceptualization problems of traditional social order in Kabarda (XVI–XVIII centuries) - Yuzanna M. Azikova (Кавказология, 2022)
This paper analyzes the ways of reconstruction and conceptualization of the traditional organization of society and power of Kabarda in the 16th–18th centuries. This work studies features of the presentation in the generalizing works of the stage-typological characteristics of the traditional society of Kabardians in the complex of socio-spatial, socio-economic and potestary-political conditions of development. Demographic, territorial and economic factors of social and political development are emphasized as key problems, being the focus of the research attention. The inconsistency of the characteristics of the social system of medieval North Caucasian societies in historiography, presented in a summary picture of the history of “mountain feudalism”, is noted. There is a tendency to reduce the analysis of the social organization of Kabardians to the problems of “features” and “level” of development of “Kabardian feudalism”. Potestary-political identification of Kabarda in the 16th–18th centuries in the sense of organizational and governance forms of institutionalization of power is emphasized as a problem that is difficult to solve. Also, attention is drawn to the development of fruitful traditions of domestic and foreign historiography associated with the study of ancient forms of statehood and institutional alternatives and analogues to the state. Successful interpretations of the social organization of traditional Kabardian society and forms of institutionalization of power are associated with modern political anthropological concepts, within which an assessment is made of the level of development of the considered traditional and archaic communities in studying complexity of the ideological, economic, social, demographic, and territorial components.